2006
DOI: 10.1029/2005gl024837
|View full text |Cite
|
Sign up to set email alerts
|

Planetary wave oscillations in mesospheric winds, equatorial evening prereversal electric field and spread F

Abstract: [1] Analysis of the MLT region winds measured by a meteor radar and the evening F region vertical plasma drift (prereversal zonal electric field -PRE) measured by digisondes over low latitude sites in Brazil, provide evidence of planetary wave (PW) scale oscillations of episodic nature simultaneously at mesospheric and F region heights. $4-day and 7-day periods are found to dominate the event analyzed. The PW scale oscillations in the PRE produces strong modulation in the equatorial spread F (ESF) irregularity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(119 citation statements)
references
References 14 publications
5
110
0
Order By: Relevance
“…Recently, Abdu et al (2006a) presented evidence for existence of planetary wave oscillations (6.5-day and 14-day) in the equatorial ionosphere. Further study by Abdu et al (2006b) indicates simultaneous 6-day wave features in the day-to-day variation of the equatorial F-region vertical drift velocity and the mesospheric winds at low-middle latitudes. It is interesting to note that they observed this in November 2002.…”
Section: -Day Wavementioning
confidence: 88%
“…Recently, Abdu et al (2006a) presented evidence for existence of planetary wave oscillations (6.5-day and 14-day) in the equatorial ionosphere. Further study by Abdu et al (2006b) indicates simultaneous 6-day wave features in the day-to-day variation of the equatorial F-region vertical drift velocity and the mesospheric winds at low-middle latitudes. It is interesting to note that they observed this in November 2002.…”
Section: -Day Wavementioning
confidence: 88%
“…Pancheva et al (2002) reported 16-day oscillation in hmF2 at mid-latitude and attributed it to the modulation of semidiurnal tide and 16-day planetary wave observed in the MLT. Abdu (2006) found that the planetary wave modulating the E region tidal winds leads to planetary-wave-scale oscillations in the plasma vertical drift velocity in the equatorial ionosphere. Recent studies revealed that quasi-16-day periodicity was observed in the equatorial mesopause and lower thermosphere temperature, electron density and TEC in EIA region, and EEJ during the same time period due to the quasi-16-day planetary wave modulating the tidal amplitudes in the ionospheric dynamo region (Vineeth et al, 2007;Pedatella and Forbes, 2009;Sripathi and Bhattacharyya, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evidence of periodic planetary waves was also demonstrated in many ionospheric parameters, including the equatorial electrojet (EEJ) index, vertical plasma drift velocities, electron density, and F layer peak height (Abdu et al, 2006;Parish et al, 1994;Vineeth et al, 2007;Fagundes et al, 2005;Pedatella and Forbes, 2009;Liu et al, 2011). For example, Abdu et al (2006) provided evidence of planetary waves with 4-day and 7-day periods in the vertical drift plasma velocity based on meteor radar and digisonde data over low-latitude sites in Brazil. Fagundes et al (2005) A series of recent reports concerning ionospheric perturbations associated with lower atmospheric forcing have focused on sudden stratospheric warming (SSW).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Planetary wave oscillations in the equatorial ionosphere are more often observed during non-SSW periods, as have been well established from numerous investigations in recent years (see for example, Forbes and Leveroni 1992;Chen 1992;Pancheva et al 2003;Takahashi et al 2009;Abdu et al 2006Abdu et al , 2015a. In their upward propagation, (waves of longer vertical wavelengths attaining higher altitude) these waves nonlinearly interact with ; b The corresponding Digisonde ionograms; c TIMED/GUVI 135.6 nm images extending in the entire longitude span showing the global distribution of the EIA brightness and the patches of brightness depletions indicating plasma bubbles symmetric on either side of the dip equator (Kil et al 2006) tidal modes whereby electric fields are generated in the dynamo region with consequent modulation of the electrodynamical coupling processes.…”
Section: The Variabilities Defining Ionospheric Weathermentioning
confidence: 77%